Assessment of the Impact of Distinct Vineyard Management Practices on Soil Physico-Chemical Properties. Issue 13 (June 2020) - Ferreira, Carla SS; Veiga, Adélcia; Caetano, Ana; Gonzalez-Pelayo, Oscar; Karine-Boulet, Anne; Abrantes, Nelson; Keizer, Jacob; Ferreira, António JD
Vines are one of the most ancient crops, with great relevance worldwide but especially in wine-growing areas in Southern Europe. In the Bairrada wine region of north-central Portugal, vineyards have long been managed intensively, with frequent tillage and application of fertilizers and phytochemical products. During the last decade, however, these conventional practices are increasingly becoming substituted by more sustainable management practices, in particular integrated production (IP) and, to a lesser degree, no-tillage (NT) and biodynamic (BD). This study investigated differences in soil quality of 4 vineyards managed with each of these practices for at least 6 years. Twelve topsoil (0-15 cm) samples were collected in vineyard rows and inter-rows, during one sampling campaign, and analyzed for selected physical and chemical properties. These physical properties were texture, bulk density and penetration resistance, while the chemical properties included pH, electrical conductivity, and the contents of organic matter, nutrients, cations, and metals. Nearby forest soils were also sampled as a reference, since this was the prior land-use in the study sites. The obtained results demonstrated that conventional practices were associated with diminished soil quality, as indicated by lower contents of organic matter and nutrients, such as total nitrogen (TN) and phosphorus (TP), and exchangeable cations, as well as by a higher concentration of Cu and, in some samples, of Ni and Pb. Cu concentrations were also relatively high under NT, so that overall soil quality, particularly associated with fertility, was best under IP.